A comparative study of mesophilic and thermophilic anaerobic digestion of municipal sludge with high-solids content: Reactor performance and microbial community. (April 2020) - Wu, Zong-Lin; Lin, Zhi; Sun, Zhao-Yong; Gou, Min; Xia, Zi-Yuan; Tang, Yue-Qin
Highlights: MAD and TAD of high-solids containing sludge were comprehensively compared. The response of microbial community composition to sludge properties was monitored. TAD performed better than MAD in biogas production and VTS reduction. Ammonia inhibition was the main risk for high-solids TAD of sludge. Microbial analysis based on RNA datasets more accurately reflected the AD process. Abstract: This study involved a comparison between mesophilic (MAD) and thermophilic anaerobic digestion (TAD) of municipal sludge with high (10%) solids content; the reactor performance and the response of total and active microbial communities to changes in sludge properties were monitored. Both TAD and MAD were stably maintained. TAD performed better than MAD in biogas production and volatile total solids reduction upon feeding sludge 1. TAD was slightly inhibited by ammonia, whereas the performance of MAD was improved when sludge 2 was used as the feedstock. Alpha- and beta-diversity analyses revealed significant differences in the microbial community based on DNA and RNA datasets, indicating that not all microbes function in AD. The active microbial community diversity and composition in MAD and TAD were also driven by sludge properties. Moreover, MAD showed significantly higher richness and diversity of the active microbial community compared with TAD, regardless of changes in sludge properties.